Pondok Pesantren Tahfizul Qur'an ˜Manba'ul Furqon: Pesantren Desa Berskala Nusantara - Ecep Badri Yunardi (SUHUF, 2008)
This writing is a description of the profile of the Islamic boarding school (pesantren) for memorizing the Qur'an (learning the Qur'an by heart or tahfiz), under the supervisory of KH Abdullah Ma'sum, which is located at village Karehkel, Leuwiliang district, Bogor regency, West Java. Some aspects being studied covers the history of its pesantren, the achievements of the pesantren, the facilities, the students, the alumni, the activities of the students, the curriculum, the method for memorizing the Qur'an being used, the intellectual networks (sanad), as well as the institution of this pesantren